Bacteria-Assisted Celastrol Liposomes for Effective Chemotherapy Against Lung Cancer in Mice Model - Wang X; Gao C; Zhang X; Gu Y; Fu S; Lin S (International Journal of Nanomedicine)
Xinyi Wang, Chao Gao, Xialin Zhang, Yingqi Gu, Shaozhi Fu, Sheng Lin Department of Oncology, the Affiliated Hospital of Southwest Medical University, Luzhou, 646000, People’s Republic of ChinaCorrespondence: Shaozhi Fu; Sheng Lin, Email shaozhifu513@swmu.edu.cn; lslinsheng@163.comIntroduction: Lung cancer has a high resistance rate to current chemotherapies. Therefore, there is an urgent need to develop new anticancer drugs. Celastrol is a promising anticancer bioactive compound for various types of cancers. However, its poor solubility and severe liver damage have limited its clinical application.Methods: BIF@CEL/LF/CMCS-Lipo (Bif@CLC-LP), a self-driving biomotor that targets tumor tissues, was used to deliver celastrol, which was encapsulated in surface-modified lactoferrin liposomes, which were then coated with carboxymethyl chitosan and loaded onto the surface of Bifidobacterium infantis (Bif). Extensive in vitro and in vivo experiments were performed to assess its physicochemical and antitumor properties and safety in treating lung cancer.Results: Bif@CLC-LP responds to pH and is bioselective, precisely targeting hypoxic regions of tumors. In the acidic tumor environment, the carboxymethyl chitosan coating breaks down, releasing liposomes that can specifically target the cancer surface receptor for endocytosis. This process increases the production of reactive oxygen species (ROS) and decreases the mitochondrial membrane potential in lung cancer cells, leading to apoptosis.Conclusion: In our work, Bif@CLC-LP significantly inhibited tumor growth while minimizing celastrol-induced liver damage in a mouse lung cancer model. This bacteria-mediated liposome delivery system is a promising new nanoplatform for treating different types of solid cancer.Keywords: bifidobacterium infantis, celastrol, liposome, lactoferrin, chemotherapy